2018
DOI: 10.1016/j.cardfail.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

LCZ696 (Sacubitril/Valsartan), an Angiotensin-Receptor Neprilysin Inhibitor, Attenuates Cardiac Hypertrophy, Fibrosis, and Vasculopathy in a Rat Model of Chronic Kidney Disease

Abstract: Highlights The effect of LCZ696 (Sacubitril/valsartan) against cardiorenal syndrome is proposed. LCZ696 more improved CKD related heart failure than valsartan therapy alone. LCZ696 attenuated CKD related cardiac hypertrophy and fibrosis and aortic fibrosis. Effects of LCZ696 for heart are mediated by anti-inflammation and oxidative stress. LCZ696 also improved indicators of mitochondrial mass/function. AbstractBackground: Chronic kidney disease (CKD) is associated with cardiac hypertrophy, fibrosis and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 32 publications
(28 reference statements)
0
50
0
Order By: Relevance
“…Potential pathophysiological mechanisms of the beneficial effects of ARNIs in myocardial diastolic function might include (a) hemodynamic improvements as a consequence of neprilysin inhibition, including natriuretic peptide‐mediated reduction in ventricular wall stress or (b) direct benefit in intrinsic myocardial diastolic properties due to attenuation of progressive ventricular remodeling and reductions in myocardial fibrosis and ventricular hypertrophy . Of note, based on the results of this study, the improvements in exercise capacity parameters and E/E′ ratio as well as the increase in Sa were not correlated with sacubitril/valsartan‐induced decrease in blood pressure.…”
Section: Discussionmentioning
confidence: 70%
“…Potential pathophysiological mechanisms of the beneficial effects of ARNIs in myocardial diastolic function might include (a) hemodynamic improvements as a consequence of neprilysin inhibition, including natriuretic peptide‐mediated reduction in ventricular wall stress or (b) direct benefit in intrinsic myocardial diastolic properties due to attenuation of progressive ventricular remodeling and reductions in myocardial fibrosis and ventricular hypertrophy . Of note, based on the results of this study, the improvements in exercise capacity parameters and E/E′ ratio as well as the increase in Sa were not correlated with sacubitril/valsartan‐induced decrease in blood pressure.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, Sac/val administration reduced cardiac fibrosis rather than cardiac hypertrophy in its protection against pathological cardiac dysfunction (Miyoshi et al, ; von Lueder et al, ). In a recent study on rats with chronic kidney disease, Sac/val was more effective than Val in reducing not only cardiac but also aortic fibrosis (Suematsu et al, ). A reduced deposition of hyaluronic acid within the ligated LCA provides new therapeutic differences between ARNI and ARB.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 60 mg/kg LCZ and 30 mg/kg valsartan was selected because several experimental studies using rat models employed these doses of valsartan and LCZ696 [16,17,21,22]. The previous studies showed greater decreases in SBP induced by LCZ696 than that by valsartan alone.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Gu et al [7] reported that plasma concentration-time profiles of valsartan are similar between administration of a single oral dose of 400 mg LCZ696 and 320 mg valsartan in healthy human participants. 60 mg/kg LCZ696 and 30 mg/ /kg valsartan was chosen, which are similar to those in previous studies of valsartan and LCZ696 in rat models [16,17,21,22], because pharmacodynamic data for LCZ696 could not be found in the ISO-treated rat model. Therefore, it cannot be denied that the pharmacodynamics of these drugs may have influencedthe present results.…”
Section: Limitations Of the Studymentioning
confidence: 99%